Synthesis of Ortho‐Functionalized Tetrachlorinated Azobenzene Phosphoramidites for Incorporation Into siRNAzos for Photocontrolled Gene Silencing. Issue 8 (23rd August 2022) - Hammill, Matthew L.; Islam, Golam; Desaulniers, Jean‐Paul
Abstract: This paper contains the detailed synthesis and characterization protocols of ortho‐ functionalized tetrachlorinated azobenzene‐containing small interfering RNAs (siRNAs), which have photoswitchable properties effectively controlled with visible light. To design this tetrachlorinated azobenzene scaffold, a late‐stage chlorination with N ‐chlorosuccinimide and palladium is used. Next, a single hydroxyl group from the tetrachlorinated azobenzene is protected with a 4, 4′‐dimethoxytrityl (DMT) group, followed by phosphitylation with 2‐cyanoethyl‐ N, N ‐diisopropylchlorophosphoramidite. These phosphoramidite monomers are compatible with automated solid‐phase oligonucleotide synthesis to generate tetrachlorinated azobenzene‐containing oligonucleotides. This paper also contains the detailed biophysical characterization, biological testing, and photo‐switching protocols of ortho ‐functionalized chlorinated azobenzene‐containing siRNAs (Cl‐siRNAzos), which have photoswitchable properties that can be controlled with visible light. First, the Cl‐siRNAzos are characterized by annealing the sense and antisense strands together and then measuring the circular dichroism (CD) profile, and the melting temperatures ( T m ) of the duplexes. Secondly, the biological testing of the Cl‐siRNAzos in cell culture is done to determine their gene silencing efficacy. Finally, their gene‐silencing activities are measured after exposure to red light in order to inactivate the Cl‐siRNAzo, and then either violet light or infrared thermal relaxation is deployed, which re‐activates the Cl‐siRNAzo. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Synthesis of 4, 4′‐bis(hydroxyethyl) ortho‐ functionalized tetrachlorinated azobenzene phosphoramidite (5 ) Basic Protocol 2 : Synthesis, purification, and characterization of siRNAs containing ortho‐ functionalized tetrachlorinated azobenzene Basic Protocol 3 : Gene‐silencing evaluation of ortho‐ functionalized tetrachlorinated azobenzene using firefly luciferase